FAKTOR-FAKTOR YANG MEMENGARUHI PILIHAN PETANI MELAKUKAN ALIH FUNGSI LAHAN USAHATANI KAKAO MENJADI USAHATANI CENGKEH - Zani, Munirwan; Yunus, Lukman; Alwi, La Ode; Gafaruddin, Abdul; Sudarmo, Hadi (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
This study aims to determine and analyze the factors that influence the choice of farmers to transfer cocoa to clove farming in Ponggiha Village, Lasusua District, North Kolaka Regency. The number of samples used in this study were 70 people.the sample used is farmers who make the transition of commodities either partially or wholly from cocoa farming toclove farming. The data analysis method used in this study is logistic regression. The results showed that from the logistic regression estimation it was known that the factors that influenced the conversion of cocoa farming into cloves were land area, age of cocoa plants, cocoa production cost, cocoa production, cocoa farming income and cocoa farming experience.